ANALISIS PEMBENTUKAN KARAKTER MANDIRI DAN HEMAT MELALUI PEMBELAJARAN IPAS BIDANG EKONOMI DALAM PERSPEKTIF BIMBINGAN DAN KONSELING (Studi pada Siswa MI Ma’arif Lengkong) - Al Darmono; Siti Jenab (AflahConsilia : Jurnal Bimbingan dan Konseling, 2026)
This study aims to describe the planning and implementation of IPAS economics education, as well as the factors that influence the development of frugal and independent character traits in students, from a counseling perspective. The study is based on the increasing consumption behavior of children of Madrasah Ibtidaiyah age that is not balanced by an adequate understanding of finances. The study employed a qualitative case study design and was conducted at MI Ma’arif Lengkong. Data were collected through observation, interviews, and document analysis. The data were analyzed using an inductive approach that included data reduction, presentation, drawing conclusions, and verification. The findings of this study indicate that although the curriculum has not been supported by systematically and measurably organized achievement indicators, it has reinforced values. Implementing experiential learning activities, such as simulations of buying and selling, savings programs, and market day activities, has helped students understand economic concepts and encouraged frugal and independent behavior. While changes in student behavior are beginning to emerge, they are not yet widespread and require continued practice. Other factors that influence character formation include teachers, school programs, and family support.